Perancangan Business Process Improvement Untuk Layanan Kepegawaian Menggunakan Domain Service Design Dalam Framework Information Technology Infrastructure Library (ITIL) V3 (Studi Pada Bank XYZ) - Citra Hemas Jati Inayu; Yusi Tyroni; Nanang Yudisetiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
XYZ Bank is a banking company with head office in Jakarta. The employment service business process for leave, overtime, and update of employee data at Bank XYZ still rely on paper based, so that the HC area unit (Human Capital) must manually input recap data into SAP (Employee Administration System). HC area unit employees will be particularly vulnerable to input errors that can be fatal for employee salary calculations. The implementation of paper based on some activities of leave, overtime, and data update also cause the process runs less efficient and effective so that the processing time becomes longer. The method used in doing business process improvement refers to the framework of ITIL v3 domain service design. The result of the business process improvement of XYZ staffing service business for leave is an average time acceleration of 58.11 minutes due to loss of PIC (Person in Charge) activity in requesting and submitting the leave leave form, as well as equalization of utilization to superiors, employees and HC area due to loss of role PIC and courier. In the employee overtime business process, the average acceleration time of 370.98 minutes due to loss of PIC's role in manual recording, as well as equitable distribution of employers, officers, and HC areas due to loss of PIC and messenger role. In the business process update employee data there is an acceleration of 22.6 minutes due to loss of activity provide the form and input employee data, and there is a change in resource utilization percentage due to reduced HC area activity.